Shareability: novel perspective on human-media interaction - Bruno, Nicola; Guerra, Giorgia; Alioto, Brigitta Pia; Jacomuzzi, Alessandra Cecilia (Frontiers in Computer Science, 2023)
Interpersonal communication in the twenty-first century is increasingly taking place within digital media. This poses the problem of understanding the factors that may facilitate or hinder communication processes in virtual contexts. Digital media require a human-machine interface, and the analysis of human-machine interfaces traditionally focuses on the dimension of usability. However, interface usability pertains to the interaction of users with digital devices, not to the interaction of users with other users. Here we argue that there is another dimension of human-media interaction that has remained largely unexplored, but plays a key role in interpersonal communication within digital media: shareability. We define shareability as the resultant of a set of interface features that: i) make sharing of materials with fellow users easy, efficient, and timely (sharing-related usability); ii) include features that intuitively invite users to share materials (sharing-related affordances); and iii) provide a sensorimotor environment that includes perceptual information about both presented materials and the behavior of other users that are experiencing these materials through the medium at hand (shared experience availability). Capitalizing on concepts from semiotics, proxemics, and perceptual and cognItive neuroscience, we explore potential criteria to asses shareability in human-machine interfaces. Finally, we show how these notions may be applied in the analysis of three prototypical cases: online gaming, visual communication on social media, and online distance teaching.